Podoba slovenskih splošnih knjižnic v letu 2009 - Vodeb, Gorazd (Knjižnica, 2010)
The 2009 Slovenian Public Library Annual Statistical Survey is presented. Data were collected and published by the Library System Development Centre at the National and University Library of Slovenia. Data on opening hours, space and equipment, size of libraries' collections and annual additions are presented. Data on visitors, registered members, loans and other library services, staff profiles and financial data are included, too. Statistical indicators are comparedto library regulations and standardsand to the goalsof the Resolution on the 2008-2011 National Programme for Culture.
Keywords: splošne knjižnice; statistični podatki; letna poročila; Slovenia; Slovenija; 2009